An Application of the Cooperative Learning Model with Guided Discovery Approach Improves Student Learning Outcomes in an Educational Statistics Course - Pertiwi, Indah (Mathematics Education Study Program, 2025)
This study aims to determine the effectiveness of the application of the Cooperative Learning model with a guided discovery approach in improving student learning outcomes in the Statistics of Education course. The research used a quantitative approach with the type of Classroom Action Research (PTK) conducted in two cycles. The research subjects were fourth-semester students of the Pamulang University Economic Education Study Program in the 2024/2025 academic year. Data were collected through learning outcomes tests, student activity observations, and student response questionnaires to the learning model. The results showed that there was a significant increase in the average value of student learning outcomes, from 69.88 in the pre-cycle to 72.76 in cycle I, and increased to 81.26 in cycle II. The percentage of learning completeness increased from 52% to 86% at the end of cycle II. Observations also showed an increase in student activeness and collaboration in the learning process with the percentage of learning implementation reaching 94%. Most students gave a positive response to the use of the Cooperative Learning model with a guided discovery approach because it was considered to encourage active participation and better understanding of the material. Therefore, it can be concluded that the Cooperative Learning model with a guided discovery approach is effectively used in learning Statistics Education to improve learning outcomes and student involvement.